UK radical prostatectomy outcomes and surgeon case volume: based on an analysis of the British Association of Urological Surgeons Complex Operations Database - Vesey, Sean G.; McCabe, John E.; Hounsome, Luke; Fowler, Sarah (BJU international, 2012)
Study Type – Therapy (outcomes) Level of Evidence 2b What’s known on the subject? and What does the study add? A slowly emerging body of urological outcome data reports lends increasing credence to the intuitive hypothesis that high volume surgeons have better surgical outcomes. This large scale prospective British Radical Prostatectomy study adds weight to this increasing body of evidence by supporting the hypothesis and also in raising the suggestion that current UK guidelines with respect to minimum surgeon case volume be significantly increased. OBJECTIVE • To undertake a detailed analysis of the British Association of Urological Surgeons (BAUS) Section of Oncology Complex Operations Database to report UK outcomes of radical prostatectomy (RP) with particular reference to the case volume of the operating surgeon. MATERIALS AND METHODS • All RP entries on the BAUS complex operations database were extracted from its commencement in January 2004 to September 2009. • Patient age, prostate‐specific antigen (PSA) levels, clinical tumour stage and biopsy Gleason score were analyzed together with operative variables, including the surgical approach, lymphadenectomy status, blood loss, hospital length of stay and individual surgeon case volume. • The postoperative variables assessed included surgical specimen Gleason score and pathological tumour stage, prostate weight and the presence of positive surgical margins (PSM), as well as evidence of biochemical recurrence. RESULTS • A total of 8032 RP cases were entered on the database and Follow‐up data was available on 4206 cases. Mean patient age was 61.8 years and the mean presenting PSA was 8.3 ng/mL. • Open RP procedures were performed on 5429 patients and laparoscopic RP on 2219. • The positive surgical margin (PSM) rate for the entire series was 38%. Analysis of PSM by pathological stage revealed a pT2 PSM rate of 24%. Multivariate analysis of variables which might affect PSM revealed pre‐operative clinical TNM stage, surgeon case volume, RP specimen Gleason score and pathological TNM stage were significant parameters (P  <  0.01). • When prostate weight and PSM status were analysed, these was a significant association between smaller prostate weight and PSM status. Interestingly, 45% of high grade Gleason 8–10 needle biopsy cancers were downgraded to Gleason scores 7 or less on RP analysis. • Analysis of annual surgeon caseload revealed that 54% of surgeons performed an average of less than 10 procedures per annum and 6% of surgeons performed an average of 30 or more procedures per annum. When individual outcome variables where examined against surgeon case activity it was demonstrated that outcomes are clearly improved beyond 20 cases and there is a trend to continued improvement up to the series maximum of 40 cases per annum. CONCLUSIONS • High volume surgeons have less peri‐operative and postoperative complications and better surgical and disease‐free outcomes than low volume surgeons. • In the UK, raising the current minimum Improving Outcomes Guidance threshold from five RP cases per surgeon per annum to no less than 20 (and ideally to 35 or more cases per annum) could potentially improve overall outcomes.